The Psychology of Rights and Duties: Empirical Contributions and Normative Commentaries.
DOI: 10.1037/10872-004
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Cultural Theory of Rights and Duties in Human Development.

Abstract: Let the jury consider their verdict," the King said, for about the twentieth time that day. "No, no!" said the Queen. "Sentence first-verdict afterwards." "Stuff and nonsense!" said Alice loudly. "The idea of having the sentence first!" -Lewis Carroll (I960, p. 161)Trials, as even the child Alice knows, follow well-established legal guidelines, and we learn about these formal rules and laws that are "on the books" in numerous ways. Black-letter law is extensive in its scope, explicit, and widely publicized and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 40 publications
1
18
0
Order By: Relevance
“…In contrast, the researchers' opinions were mainly rooted in scientific discourse and prioritized the project itself through values such as taking responsibility for the research project. This finding is also in line with earlier findings that described a general trend of when groups with different power positions are positioned against each other; the less powerful focus on rights and the more powerful on duties, which explained why the users in the current study focused on rights while the researchers focused on duties.…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, the researchers' opinions were mainly rooted in scientific discourse and prioritized the project itself through values such as taking responsibility for the research project. This finding is also in line with earlier findings that described a general trend of when groups with different power positions are positioned against each other; the less powerful focus on rights and the more powerful on duties, which explained why the users in the current study focused on rights while the researchers focused on duties.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, individual rights and duties lie at the core of the social contract that links the individual to the state. While institutions do not recognize the active role of the individual dealing with society, it is likely that there is a clash between rights and duties, such that the institutions will give priority to citizens' duties, while citizens will stress their personal rights (Moghaddam, 2003;Moghaddam & Riley, 2005).…”
Section: Rights and Dutiesmentioning
confidence: 99%
“…International analyses of the Declaration have shown similar loadings on the proposed four factors (Doise, Spini, Jesuino, Ng, & Emler, 1994) with a followup study finding a two-factor cluster between individual and social rights (Doise, Spini, & Clémence, 1999). While there is cultural variation regarding human rights support and support for specific rights (Hoppe-Graff & Kim, 2005;Moghaddam & Riley, 2005;Moghaddam & Vuksanovic, 1990;Passini, 2014;Passini & Emiliani, 2009;Worchel, 2005), a general review of all human rights research confirmed strong international support for human rights (McFarland, 2015) and definitions of human rights violations (Clémence, Devos, & Doise, 2001;Spini & Doise, 1998.…”
Section: The Historical Basis For a Psychology Of Human Rights And Pementioning
confidence: 99%